Research and thesis: if only I had known - Talib, Othman (MPWS Rich Resources, 2014)
This book should be owned and read by all undergraduates, master and Ph.D. students who are currently involved in thesis writing or planning to embark on conducting research. This book is a must-have for tutors, research assistants, and lecturers in higher institutions especially those involved in student supervision. The book contains the nuts and bolts of carrying out research and thesis writing. No other copy in the bookstore has ever been published with practical examples using easy-to-understand language. Definitely the ultimate guide for those who have lost their way in research.